2019
DOI: 10.15640/jsbed.v7n1a3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Record Keeping On the Performance of Selected Small and Medium Enterprises in Lagos Metropolis

Abstract: The importance of Small and Medium Enterprises (SMEs) in many economies cannot be over emphasized as they play vital roles in the economy of both developed and developing countries such as employment generation and poverty reduction among others. However, majority of SMEs have failed to recognize the importance of well-structured accounting system that would have enabled them keep accurate financial statement. The study set out to analyse the extent to which accounting information is being used to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…These findings implied that majority of the commercial banks carried out financial statement lending to SMEs. The results concurred with the findings of Aladejebi and Aladimeji (2019) affirming that absence of correct financial statement makes SMEs vulnerable in securing bank loans. The business information of the SMEs was the major factor that the bank required to give a loan (Saleh, Alkasasbeh & Bader, 2017).…”
Section: Descriptive Analysissupporting
confidence: 88%
“…These findings implied that majority of the commercial banks carried out financial statement lending to SMEs. The results concurred with the findings of Aladejebi and Aladimeji (2019) affirming that absence of correct financial statement makes SMEs vulnerable in securing bank loans. The business information of the SMEs was the major factor that the bank required to give a loan (Saleh, Alkasasbeh & Bader, 2017).…”
Section: Descriptive Analysissupporting
confidence: 88%
“…It found the SMEs maintaining proper records of their financial transactions, which improved their financial performance significantly. Similarly, Aladejebi and Oladimeji (2019) examined the application of accounting information to assess the performance of SMEs in Lagos Metropolis, Nigeria. The data were collected through the administration of 200 questionnaires to 200 SME owners out of which 197 were returned.…”
Section: Review Of Empirical Studies On Business Recordkeeping Practices In Africamentioning
confidence: 99%
“…Therefore, business zakat could only be fairly and correctly calculated if complete and proper records of business transactions are kept. However, a number of African studies, such as Zotorvie (2017), Pavtar (2017), Nketsiah (2018), Nyathi et al (2018) and Aladejebi and Oladimeji (2019), among others, found enterprises maintaining either improper or incomplete records. Although these studies did not evaluate the recordkeeping of zakatable assets, it can be inferred that there is a tendency to underpay enterprise zakat.…”
Section: Introductionmentioning
confidence: 99%
“…Ademola et al [11] reported that most of the SSEs do not keep records of their business transactions, and when they do, the records are not kept properly. Without financial statements, access to loans from banks is reduced [12]. Information provided through record keeping enable managers and owners of SSEs to make business decisions.…”
Section: Introductionmentioning
confidence: 99%